The Influence of Organizational Commitment, Training, and Motivation on Employee Performance - Susanti, Ervin Nora; Suryalisman, Suryalisman; Hakim, Lukmanul; Ratnasari, Sri Langgeng; Fujiantoro, Avilia Pradesti; Mulyadi, Aris; Amira, Amira; Sutjahjo, Gandhi (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This research aims to determine and analyze the influence of leadership style, organizational commitment, training and discipline on the performance of Batam City Highways and Water Resources Department employees. The population of this study was 50 employees of the Batam City Highways and Water Resources Department. Sampling uses saturated sampling or census, which is a sampling technique when all members of the population are used as samples. This research is quantitative research, with multiple linear regression statistical analysis. The research results show that Organizational Commitment, Training and Motivation partially has a positive and significant effect on employee performance. Simultaneously, organizational commitment, training and motivation have a significant effect on employee performance.